ANALISIS KEUNTUNGAN USAHA RUMAH MAKAN EL-SHADAI DI KAWASAN WISATA KULINER â€œWAKEKE MANADOâ€ - Grace Masengi; Celcius Talumingan; Grace A.J. Rumagit; Melissa L.G. Taroreh (COCOS, 2014)
Grace Masengi. Feasibility Analysis of El-Shadai Retaurant Business in The Area Culinary Tourism of â€œ Wakeke Manadoâ€. Under the guidance of Celcius Talumingan a chairman, and Grace. A. J. Rumagit, and Melissa L.G. Tarore as memberâ€™s).The objective of this research is to analyze the feasibility of El-Shadai restaurant to know, in detail, the business activity profile and the amount of the profit achieved every month, that it can also be known wheter it is feasible or not this El-Shadai Restaurant Business in the area of culinary tourism of â€œWakeke Manadoâ€ to be maintained. This research used primary data which was obtainedby direct interview to the business owner containing the list of questions, and the secondary data was obtained from the governmental institution related to this research, that was Sub-district office of Wenang Utara. The data analysis methodused was Descriptive analysis method, data collected was presented in table form, and then used business profit analysis, also continued with the analysis Return of Cost Ratio to analyze the feasibility of El-Shadai restaurant business.This research result showed that entirely the El-Shadai restaurant business has the profit of Rp. 13.829.942 each month, with the cost ratio R/C of 1,33. Therefore it can be concluded that culinary business is categorized to be feasible to run because of the R/C value is more than 1. This shows that every Rp. 1 of production expense spent by the restaurant manager can give the return as the income of Rp. 1,33. It means that the total income is larger than total production expense and this culinary business activity still have the profit each month.